"Lost" Causes: Agenda Vetting in Global Issue Networks and the Shaping of Human Security - Charli Carpenter (Cornell University Press, ILR Press, 2014)
children born of war rape, I sat in a meeting in Cologne, Germany, where human rights activists from several countries discussed strategies for addressing the social problems faced after armed confl icts by children fathered by foreign soldiers.1 The meeting had been organized by social scientists at the University of Cologne and a Norwegian nongovernmental organization (NGO) concerned with adult â€œwar children.â€ The event drew together researchers from eastern Europe, the United States, and Africa to â€œconsolidate the evidence baseâ€ on â€œchildren born of warâ€ and develop a strategy for policy changes to address the needs of this population. Present also at the meeting was a representative from the United Nations Childrenâ€™s Fund (UNICEF), and much discussion centered on whether the United Nations, and UNICEF in particular, should pay attention to the â€œwar childâ€ population. Over the course of the two days, the UNICEF representative consistently argued against this idea, stressing a variety of organizational, conceptual, and logistical issues. Toward the end of the conference, despite case data, statistical evidence, and eloquent rights-based arguments by several of the activists at the conference, the UNICEF representative stated, â€œI remain to be convinced of the merit of UNICEF treating these children as a specifi c group.â€2 What struck me about this interaction was the power dynamic between an elite bureaucrat from a highly infl uential node in the child rights networkâ€” UNICEFâ€”and the less powerful, less well-connected entrepreneurs championing the cause of an overlooked group. I dwelt on this at some length in a chapter of my subsequent book, Forgetting Children Born of War. That book did not focus on advocacy networks specifi cally but rather on the entire set of institutions involved in constructing narratives of women and children in postwar Bosnia. Still, the question of how issues come to the attention of global advocacy organizationsâ€”and the signifi cance of certain organizations in promoting or blocking such emergent ideasâ€”caught my attention, given a general optimism at the time about the power of â€œtransnational advocacy networksâ€ in global norm-building. If advocacy networks were such an obvious force for good and a natural vehicle for individuals to mobilize pressure for social change from recalcitrant states, then how could we explain why so many causes got overlooked, even when norm entrepreneurs went to great lengths to format and present new ideas to these very networks?